Serological and Molecular Detection of Hepatatitis B Virus Among Pregnant Women in Bokkos L.G.A, Plateau State - Melisa, David Adoro; Chukwu, O. O. Chukwu; Otumala, John Egbere; Pam, Dachung Luka; Barde, Israel Joshua (European Journal of Applied Sciences, 2023)
Hepatitis B virus is a partially double stranded DNA virus that belongs to the family Hepadnaviridae. It is transmitted majorly by vertical/perinatal and horizontal transmission. HBV in pregnancy is of great public health concern as it exposes the infant to higher risk of chronic hepatitis infection, low birth weight and prematurity, resulting to morbidity and mortality. This study was aimed at determining the prevalence ofhepatitis B virus among pregnant women in Bokkos Local Government Area of Plateau State, Nigeria. Five (5) mls of venous blood samples were collected from each of the 200 participants that consented to this study, both those attending antenatal clinic and those who do not. A questionnaire was used to collect participant’s data prior to sample collection. Gynecology unit of Dung Hospital, Primary Health Center, and Cottage Hospital were used as sample collection units. All samples collected were transported to and analyzed at the molecular laboratory unit (Biotechnology unit) of National Veterinary Research Institute (NVRI), Vom. Blood sample from each participant was screened for HBsAg, using HBsAg rapid test kit (PROMED HBSAG test strip, Manufactured for Fittrust NIG Ltd, China). All HBsAg positive samples were further analyzed for the presence of HBeAg and HBV DNA via conventional PCR. The overall sero- prevalence of hepatitis B virus among pregnant women in Bokkos Local Government Area was 10% (20/200). Prevalence of HBeAg among sero-positive pregnant women was 10% (2/20). And 35% (7/20) of the sero-positive samples were positive for HBV DNA test. Age group of 30-39 years has the highest prevalence rate of HBV infection (18.8%). Age, marital status, educational level and occupation showed no significant association with HBV infection, as analyzed by chi-square test (P>0.05). Contact with infected blood or body fluid, blood transfusion, unprotected sex, exposure to environmental objects, born of HBV positive mother and HBV status of sex partner showed no significant association with HBV, (P>0.05). However, significant association with HBV infection was observed in having close relation with HBV infection (P=0.002, (P<0.05)), with highest prevalence of 20% in those who admitted to having a close relation with HBV infection and prevalence of 5.7% in those who do not have close relations with HBV. HBV vaccination status of participants was significantly associated with HBV infection (P=0.017, (P<0.05)), with higher prevalence of 7.4% among those who have not been vaccinated and 0% in those vaccinated. In conclusion, the high prevalence rate of HBV among pregnant women within the sexually active and fertile age group in this study indicates high risk of vertical transmission. This may contribute greatly to the rate of developing chronic hepatitis B infection, not just in Bokkos Local government area but in the country at large. Hence the needs for the implementation of stringent measures by the health care providers and the governments towards breaking this route of transmission and the management of this infection. This will contribute greatly towards the achievement of the WHO’s goal of eliminating viral hepatitis B by 2030.